Phylogenomics Based on Transcriptome Data Provides Evidence for the Internal Phylogenetic Relationships and Potential Terrestrial Evolutionary Genes of Lungfish - Zhao, Linlin; Wang, Shouqiang; Lou, Fangrui; Gao, Tianxiang; Han, Zhiqiang (Frontiers in Marine Science, 2021)
The evolutionary relationships of lungfish can provide crucial information on the transition from Sarcopterygii to tetrapods. Phylogenomics is necessary to explore accurate internal phylogenetic relationships among all lungfish species. In the context of the lack of genome-wide genetic information for Protopterus amphibious, we are the first to systematically report the transcriptome of P. amphibius and these sequences can be used to enrich the genome-wide genetic information of lungfish. Meanwhile, we also found significant differences in the expression levels of 3,189 genes between the lung and heart of P. amphibious. Based on phylogenomics, 1,094 shared orthologous genes were identified and then applied to reconstruct the internal phylogenetic structure of lungfish species. The reconstructed phylogenetic relationships provide evidence that lungfish is the sister group of terrestrial vertebrates and that Neoceratodus forsteri is the most primitive lungfish. Moreover, the divergence time between the most primitive lungfish and other lungfish species is between 186.11 and 195.36 MYA. Finally, 43 protein metabolism-related, stress response-related, and skeletogenesis-related genes were found to have undergone positive selection and fast evolution in N. forsteri. We suspected that these genes possibly helped ancient fish adapt to the new terrestrial environment and ultimately contributed to its spreading to land.